2008
DOI: 10.1080/10888700802330093
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zoo Visitor Presence on the Behavior of Captive Indian Gaur (Bos gaurus gaurus) in a Zoological Park

Abstract: Visitors to zoos can be a source of potential disturbance and stress to some captive, nonhuman animals in the wild. To determine the influence of visitor presence on captive bison (Bos gaurus gaurus), the study analyzed the behavior of 4 individuals at the Arignar Anna Zoological Park, India. The study often observed the behavior of the animals on visitor-present days and on days when visitors were absent. In the presence of zoo visitors, the bison showed a higher level of intragroup aggression and moving beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
2
14
2
1
Order By: Relevance
“…The decreased inactivity in the pigs in this study is similar to findings of increased activity under conditions of greater visitor pressure in zoo-housed gaur (Sekar et al, 2008), and blackbuck (Rajagopal et al, 2011). Conversely both of these species, and also gazelles (Mansour et al, 2000), showed higher aggression under the same conditions, whereas the pigs in this study showed lower aggression.…”
Section: The Presence Of Visitors Affects Vietnamese Pot-bellied Pig supporting
confidence: 73%
See 1 more Smart Citation
“…The decreased inactivity in the pigs in this study is similar to findings of increased activity under conditions of greater visitor pressure in zoo-housed gaur (Sekar et al, 2008), and blackbuck (Rajagopal et al, 2011). Conversely both of these species, and also gazelles (Mansour et al, 2000), showed higher aggression under the same conditions, whereas the pigs in this study showed lower aggression.…”
Section: The Presence Of Visitors Affects Vietnamese Pot-bellied Pig supporting
confidence: 73%
“…Some felids, for example, appear to show little or no behavioural response to visitors (Margulis et al, 2003, O'Donovan et al, 1993, whereas other studies report a visitor density influence on the behaviour of zoo-housed cats Chellam, 2002, Sellinger andHa, 2005). Ungulates have not been widely studied in this context, but sika deer (Cervus nippon; Shen-Jin et al, 2010) and Soemmerring's gazelle (Gazella soemmerringii; Mansour et al2000) both show increased alertness as visitor density increases, and higher levels of aggression have been found in gaur (Bos gaurus gaurus; Sekar et al, 2008) and blackbuck (Antilope cervicapra; Rajagopal et al, 2011) when visitor pressure is high.…”
mentioning
confidence: 90%
“…The literature on captive animals indicates that fear-provoking stimuli may lead to redirected behaviours such as aggression and abnormal behaviours (Mason, 1991;Olsson et al, 2011), behaviours that are likely associated with a range of negative emotions, such as frustration and anger (Broom and Johnson, 1993;Mellor, 2012;Van Loo et al, 2003). Interestingly, increases in intra-group aggression under high visitor numbers has been reported in a range of species including Indian gaur (Sekar et al, 2008), ring-tail lemurs (Chamove et al, 1988), Indian blackbuck (Rajagopal et al, 2011) and gorillas (Wells, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…GPS-collars in this study described both nocturnal and diurnal patterns of captive coyotes. While it is beneficial to obtain information without human disturbance (Larsen, Sherwen, and Rault, 2014;Sekar, Rajagopal, and Archunan, 2008), GPS-collars only depict location and lack information on animal behavior. Behavioral assessments can help explain the functionality of resources in relation to the animal's inherent natural tendencies.…”
Section: Discussionmentioning
confidence: 99%